The associations of phonological awareness, morphological awareness, orthographic awareness and RAN with Hong Kong Chinese children's literacy performance at word level. Issue 2 (2nd July 2016) - Liu, Duo; Zhu, Xiaoqin
ABSTRACT: The present study investigated the relations between some literacy-related cognitive skills and children's performance in Chinese reading and writing at word level. A total of 128 Hong Kong Chinese children in third and fifth grades participated in this study. Rapid automatic naming (RAN) and morphological awareness accounted for unique variance in Chinese reading accuracy and reading fluency, while RAN and phonological awareness explained unique variance in Chinese spelling, after controlling for children's age, non-verbal IQ and vocabulary. Moreover, the effects of RAN on reading fluency and spelling, as well as the effect of phonological awareness on spelling, remained significant, whereas the effect of morphological awareness on reading fluency became non-significant when reading accuracy was further controlled. These findings underscore the importance of RAN in Chinese children's literacy development, and the potential different contributions of metalinguistic skills to Chinese word reading and writing.